Mechanism of d-Cycloserine Action: Transport Systems for d-Alanine, d-Cycloserine, l-Alanine, and Glycine - Wargel, Robert J. (1970)
The accumulation of d-alanine, l-alanine, glycine, and d-cycloserine in Escherichia coli was found to be mediated by at least two transport systems. The systems for d-alanine and glycine are related, and are separate from that involved in the accumulation of l-alanine. d-Cycloserine appears to be primarily transported by the d-alanine-glycine system. The accumulation of d-alanine, glycine, and d-cycloserine was characterized by two line segments in the Lineweaver-Burk analysis, whereas the accumulation of l-alanine was characterized by a single line segment. d-Cycloserine was an effective inhibitor of glycine and d-alanine accumulation, and l-cycloserine was an effective inhibitor of l-alanine transport. The systems were further differentiated by effects of azide, enhancement under various growth conditions, and additional inhibitor studies. Since the primary access of d-cycloserine in E. coli is via the d-alanine-glycine system, glycine might be expected to be a better antagonist of d-cycloserine inhibition than l-alanine. Glycine and d-alanine at 10(−5)m antagonized the effect of d-cycloserine in E. coli, whereas this concentration of l-alanine had no effect.